2010
DOI: 10.1186/1472-6823-10-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endothelial progenitor cell function in type 2 diabetes with good and poor glycemic control

Abstract: BackgroundEndothelial progenitor cells (EPCs) play an important role in vascular repair and a decrease in the number of EPCs is observed in type 2 diabetes. However, there is no report on the change of EPCs after glycemic control. This study therefore aimed to investigate the EPC number and function in patients with good and poor glycemic control.MethodsThe number of EPCs was studied using flow cytometry by co-expression of CD34 and VEGFR2. The EPCs were cultured and characterized by the expression of UEA-I, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 43 publications
2
32
0
7
Order By: Relevance
“…7 Diabetes mellitus adversely affects the function of several adult stem cell populations from noncardiac tissues. [8][9][10][11] Resident CSC abundance has been shown to negatively correlate with type 2 diabetes mellitus. 12 Studies on diabetic bone marrow-derived angiogenic cells have revealed that increased dicarbonyl stress may be causally linked to diabetes mellitus-associated cellular dysfunction.…”
mentioning
confidence: 99%
“…7 Diabetes mellitus adversely affects the function of several adult stem cell populations from noncardiac tissues. [8][9][10][11] Resident CSC abundance has been shown to negatively correlate with type 2 diabetes mellitus. 12 Studies on diabetic bone marrow-derived angiogenic cells have revealed that increased dicarbonyl stress may be causally linked to diabetes mellitus-associated cellular dysfunction.…”
mentioning
confidence: 99%
“…Further, the number and function of EPCs in patients with good glycemic control were recovered compared with those with poor glycemic control. When glucose was supplemented to in vitro cultures, there was a negative effect on the proliferation and viability of EPCs, in a dose-dependent manner, whereas the enhancement of apoptosis was observed (Churdchomjan et al, 2010). All these deleterious effects were reported to occur due to a direct effect of elevated glucose levels on EPCs , however it was also suggested that hyperglycemia may promote EPCs dysfunction indirectly through the induction of Reactive Oxygen Species (ROS) overproduction and increased oxidative stress (Callaghan et al,.…”
Section: Hyperglycemiamentioning
confidence: 99%
“…Кардиология чество CD34+/VEGFR2+ клеток было в 2,8 раза больше, чем при декомпенсированном СД2 (HbA 1c =9,2±1,4%) и меньше в 1,5 раза по сравнению с контрольной группой [33]. В нашей работе повы-шение количества ЦПК в крови больных ИБС+СД2 комп./суб-комп.…”
Section: сахарный диабетunclassified